Role of scaling combination of risk factors in clinical and imaging findings during pregnancy in predicting placenta accreta spectrum - Afsaneh Mohammadi; Zinatossadat Bouzari; karimollah Hajian-Tilaki; Mehrdad Nabahati; Raheleh Mehraeen (Babol University of Medical Sciences, 2022)
Background: Placenta accreta is one of the known causes of maternal mortality and morbidity. If diagnosed before delivery, appropriate actions can be taken. The aim of this study was to investigate the role of scaling combination of risk factors in predicting placenta accreta spectrum (PAS). Methods: In this cross-sectional study, 120 pregnant women with two criteria and more of placenta previa in their ultrasound, underwent MRI. Clinical scores (history of surgery, cesarean section, previa, etc.) and paraclinical scores (ultrasound and MRI) were recorded and combined. In cases of hysterectomy, pathological examination was performed. The results were compared and analyzed using SPSS Version 22. The significance level was less than 0.05. Results: Of the120 studied patients, 90 (75%) women were diagnosed with placenta previa in which, 32(36%) patients had placenta accreta and 12 patients had placenta accreta without placenta previa. The mean ultrasound score in women without and with placenta accreta were 0.05±0.32 and 2.43±1.83 (p<0.001). The mean MRI score in women without and with placenta accreta were 0.05±0.27 and 2.07±2.02, respectively. The cut-off point, sensitivity and specificity were 0.50, 100% and 93.4%, respectively. The mean clinical score without and with placenta accreta were 1.97±1.32 and 4.89±3.21, respectively. The cut-off point, sensitivity and specificity were 2.50, 70% and 80%, respectively. The cut-off point of combination score, sensitivity and specificity were 3.50, 89%, 83%. Conclusion: The results of the present study showed that the most specific test to confirm the definitive diagnosis of placenta accreta is paraclinical score, alone.